(untitled) (International Seven Journal of Health Research, 2024)
Median arcuate ligament syndrome or Dunbar’s Syndrome is a rare pathology, not very prevalent in the population, whose non-specific symptoms contribute to diagnostic difficulty, presenting markedly intense abdominal pain and attributing disability to the affected individuals. Together, postprandial abdominal pain, weight loss and abdominal murmur characterize the symptomatological triad. Contrast-enhanced imaging methods are the best choice for identifying the pathology, especially angiography. To treat this disease, Dunbar suggested surgery in 1965 and to this day it remains the best method of resolving the problem, whether by open or laparoscopic means.